Vesiculobullous Diseases in a Patient with Systemic Lupus Erythematosus; [Enfermedad Vesículo-Ampollar en Una Paciente Con Lupus Eritematoso Sistémico] - Pena-Baeza, A (Ediciones Doyma, S.L., 2024)
[No abstract available]